Stop the clock - Keene, Carolyn (New York : Aladdin Paperbacks, 2005)
As the Mahoney Library's seventy-fifth anniversary celebration is being planned, a beautiful old clock, the very centerpiece of the library, is stolen and Nancy Drew is asked to help solve the crime.
Ages 8-12.
Accelerated Reader AR
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Clocks and watches -- Fiction; Mystery and detective stories; Mystery fiction